Feasibility of conducting a pilot randomized trial of a mindfulness-based intervention among sheltered young adults experiencing homelessness - Santa Maria, Diane; Cuccaro, Paula; Sibinga, Erica; Bender, Kimberly; Jacko, Ethel; Liyanage, Widumini; Jones, Jennifer; Cron, Stanley (Frontiers in Psychology, 2025)
PurposeYouth experiencing homelessness (YEH) are an underserved and difficult-to-reach population that experiences a disproportionate burden of trauma and stress compared to their housed peers. Prolonged trauma and stress can impact the development of negative emotions, reactive stress responses, and impulsive decision-making, which can lead to risk-taking behaviors. Growing research shows that Mindfulness-Based interventions (MBIs) can improve coping, impulsivity, emotion regulation, and executive function although no MBIs tailored for YEH have been tested.MethodsWe conducted a pilot attention-control randomized trial to test the feasibility and acceptability of an adapted MBI, .b4me (pronounced dot be for me), for youth living in a homeless shelter. .b4me is a five-session MBI adapted to address the unique considerations of YEH. We randomized youth to .b4me or the control condition, Healthy Topics. Each curriculum comprised 5 h-long group lessons delivered by trained facilitators. Pre- and post-lesson assessments were collected, as well as baseline, immediate-, 3- and 6-month post-follow-ups. Benchmarks for feasibility and acceptability were set a priori, and survey measures to assess emotional and psychological well-being were tested for feasibility and appropriateness of using these measures in future trials among this population and in a shelter setting.ResultsThe mean age of participants (N = 90) was 21.5 years old, with the majority identifying as male (62.2%), non-Hispanic (71.1%), black (50.0%), and heterosexual (55.6%). All a priori feasibility and acceptability benchmarks were surpassed and the reliability of most of the emotional and psychological well-being measures was confirmed.ConclusionThis study demonstrates that an MBI tailored for YEH, .b4me, is acceptable, and it is feasible to conduct a pilot attention control randomized trial with YEH living in a shelter despite major environmental obstacles.